2005
DOI: 10.1007/s00535-005-1705-x
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal repair and growth factors: recombinant human hepatocyte growth factor as an innovative therapy for inflammatory bowel disease

Abstract: The repair of intestinal mucosal injuries is a tightly regulated process involving epithelial restitution, cell proliferation and maturation, and the dedifferentiation of epithelial cells. Deeper injuries also require additional repair mechanisms, including inflammatory processes, angiogenesis, and extracellular-matrix deposition. Once intestinal mucosal injury occurs, numerous growth factors and cytokines, including hepatocyte growth factor (HGF), keratinocyte growth factor, endothelial growth factor, epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 76 publications
(76 reference statements)
1
56
0
1
Order By: Relevance
“…HGF has also been shown to be upregulated during IBD. Interestingly, administration of human HGF and HGF gene therapy decrease disease severity in experimental colitis, an effect that is opposite of that of most growth factors during IBD (13,62). These data combined with the VEGF data indicates growth factors as primary mediators of inflammation induced angiogenesis in experimental and human IBD.…”
Section: Angiogenic Mediators In Ibd and Experimental Colitismentioning
confidence: 87%
“…HGF has also been shown to be upregulated during IBD. Interestingly, administration of human HGF and HGF gene therapy decrease disease severity in experimental colitis, an effect that is opposite of that of most growth factors during IBD (13,62). These data combined with the VEGF data indicates growth factors as primary mediators of inflammation induced angiogenesis in experimental and human IBD.…”
Section: Angiogenic Mediators In Ibd and Experimental Colitismentioning
confidence: 87%
“…No mRNA for the FGF7 gene was detected in colon of dextran sodium sulfate challenged pigs (another model of IBD) fed a control diet or diets supplemented with n − 3 PUFA (no data was available for n − 6 PUFA) despite increased colonic tissue regeneration [43]. This result indicates that epithelial regeneration may in this case be FGF7-independent although its occurrence might depend on other growth factors and cytokines [44]. In the Bassaganya-Riera and Hontecillas study [43], an n − 3 PUFA-enriched diet failed to protect from IBD, and instead promoted remission from IBD possibly by activating PPAR␦.…”
Section: Discussionmentioning
confidence: 99%
“…Third, although admittedly still debated in terms of prevalence, individuals with autism can present complex medical profiles, such as gastrointestinal, immune, and nonspecific neurological dysfunctions (14,15). In addition to brain development, the pleiotropic MET receptor tyrosine kinase has specific roles in digestive system development and repair (18,23,24) and modulation of T cell-activated peripheral monocytes and dendritic antigen-presenting cells (20,22). We raise the possibility, still to be tested, that increased risk for autism, due to a functional polymorphism in the MET gene, may impart in certain individuals shared etiology of a parallel, although independent, disruption of brain and peripheral organ development and function.…”
Section: Discussionmentioning
confidence: 99%
“…MET is best understood for its role in the metastasis of a variety of cancers (16), due to somatic gain-of-function mutations, and in mediating hepatocyte growth factor (HGF)͞scatter factor signaling in peripheral organ development and repair (17)(18)(19). MET signaling contributes to immune function (20)(21)(22) and gastrointestinal repair (18,23,24). Recent studies by our group and others revealed that MET also contributes to development of the cerebral cortex (25,26) and cerebellum (27), both of which exhibit developmental disruptions in autism (28,29).…”
mentioning
confidence: 99%